Why every fly counts : a documentation about the value and endangerment of insects - Reckhaus, Hans-Dietrich (Springer, 2017)
This book discusses the beneficial and harmful effects of insects and explains their development and significance for biodiversity. Threatening pests or threatened beneficials? Biting midges are wonderful insects. The animals are so tiny and uniquely shaped that they are particularly good at pollinating the small and tight flowers of the cocoa tree. Without them, there would be much less chocolate. We associate other insects more with the damage that they cause. Mosquitoes and wasps bite us. Moth larvae damage textiles and contaminate foods. Ants undermine our paths and flies are just a pain. But what exactly is our relationship with insects? Are they more beneficial or harmful? What role do they play in the world? What are the effects of climate change: Will the number of insects continue to increase?
Keywords: Insects.; Beneficial insects.; Predatory insects.; Endangered species.; Insects -- Ecology.; elektronické knihy; electronic books